Handling conflicts over the regulation of project's time-cost risks via a simulation-based decision-making support system module. (15th March 2019) - Laslo, Zohar; Laslo-Roth, Roni; Gurevich, Gregory
Project management must consider tradeoffs of risks regarding performance, time, and cost. These tradeoffs may often cause conflicts between the project stakeholders. When decision outcomes are ambiguous and time is pressing, decision-makers may use controversial conflict resolution strategies that are often detrimental, changing conflicts that have constructive potential into those that are unhealthy. We propose a simulation-based DMSS module that can be used to quickly analyse the risks of alternative project plans. Its implementation can reduce the usage of controversial conflict resolution strategies and focus, instead, on one of the cooperation strategies that can enhance performance and well-being at work. Whereas meeting technical specifications is a non-negotiable demand, we can make do with a two-dimensional tradeoffs model - consider tradeoffs between time and cost risks. Thirteen of 17 implementations of the DMSS module hinted that this tool may be beneficial in preventing conflict escalations (a numerical example is given).